Efektivitas Iklan TikTok dalam Meningkatkan Brand awareness di Kalangan Generasi Z: Studi Kasus Mahasiswa Institut Agama Islam Al-Zaytun Indonesia - Nabilah Kurnia; Elang Bakhrudin; Supriadi M. (Lembaga Pengembangan Kinerja Dosen, 2025)
This research explores the effectiveness of TikTok advertising in enhancing brand awareness among Generation Z students at IAI AL-AZIS. The study employs a descriptive qualitative approach through in-depth interviews, direct observations, and documentation to capture comprehensive insights. The analysis is framed using Uses and Gratifications Theory, the Hierarchy of effects Model, and Persuasive Communication Theory. Findings indicate that TikTok advertising successfully builds brand awareness through three stages: cognitive, affective, and conative. Advertisements that appear authentic, light, and contextually relevant to students are considered the most impactful. However, several challenges emerge, such as monotonous content, overpromising messages, and a lack of transparency, which can reduce credibility. The research further emphasizes that TikTok, while commonly perceived as an entertainment platform, has shifted into a strategic medium for marketing communication, particularly for young audiences. Importantly, when integrated with Islamic values—such as honesty, usefulness, and simplicity—TikTok advertising not only influences consumer perception but also contributes to ethical communication practices in a digital context.